2016
DOI: 10.1371/journal.pone.0157470
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Willingness to Pay for Health Insurance in Low and Middle Income Countries

Abstract: ObjectiveAccess to healthcare is mostly contingent on out-of-pocket spending (OOPS) by health seekers, particularly in low- and middle-income countries (LMICs). This would require many LMICs to raise enough funds to achieve universal health insurance coverage. But, are individuals or households willing to pay for health insurance, and how much? What factors positively affect WTP for health insurance? We wanted to examine the evidence for this, through a review of the literature.MethodsWe systematically searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
4
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 40 publications
8
102
4
3
Order By: Relevance
“…Data was collected using an interview questionnaire which was prepared by reviewing similar WTP studies and modified to fit the local context (8,11,(16)(17)(18)(19)(20)(21)(22). It was pretested among 10% of the sample size of the study participants, which were not included in the actual study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data was collected using an interview questionnaire which was prepared by reviewing similar WTP studies and modified to fit the local context (8,11,(16)(17)(18)(19)(20)(21)(22). It was pretested among 10% of the sample size of the study participants, which were not included in the actual study.…”
Section: Methodsmentioning
confidence: 99%
“…If the answer was "yes," the interviewer increased the bid by 1% until the respondent says "no" and vice versa. Finally, those who chose 3% and above are considered as WTP yes (16,17,23).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there is no clear enforcement mechanism by which to ensure enrolment under a compulsory approach for the informal sector. Finally, a recently published systematic review of WTP for health insurance in low‐ and middle‐income countries found that the WTP for health care insurance among rural households to be just below 2 per cent of GPD per capita (Nosratnejad, Rashidian and Dror, ). In Cambodia, 2 per cent of GPD per capita equates to USD 14.98 per year, or just USD 3.48 per person per year.…”
Section: Discussing and Interpreting The Resultsmentioning
confidence: 99%
“…Nevertheless, enrollment in the MHI plan priced at levels for which clients had previously reported WTP remained low. A growing body of research suggests that WTP surveys frequently underestimate actual willingness or ability to pay, yet administrative data and key informant interviews suggested other factors may ultimately limit interest and use of outpatient services . For example, few clients reported seeking care from outpatient providers covered by the health insurance, citing lost time, transportation costs, and the opportunity costs of lost income.…”
Section: Discussionmentioning
confidence: 99%